Aggrecan, IL-1β, IL-6, and TNF-α profiles in the Articular Cartilage of Miniature Horses with Chondrodysplastic Dwarfism - Basso, Roberta M. [UNESP]; Andrade, Danilo G.A. [UNESP]; Alves, Carlos E.F. [UNESP]; Laufer-Amorim, Renée [UNESP]; Borges, Alexandre S. [UNESP]; Oliveira-Filho, Jose P. [UNESP] (Elsevier, 2021)
Dwarfism is a skeletal disorder that causes abnormal growth. In Miniature horses, dwarfism can occur as chondrodysplastic dwarfism, an autosomal recessive disorder associated with five mutations (D1, D2, D3*, D4 and c.6465A > T variant) in the aggrecan (ACAN) gene. The aim of this study was to evaluate the expression of aggrecan (at the gene and protein level) and specific cytokines (IL-1β, IL-6, and TNF-α) in the articular cartilage of Miniature horses with chondrodysplastic dwarfism (D4/c.6465A > T genotype). Metatarsal bone samples from eight dwarf Miniature horses were collected for histopathological analysis, and articular cartilage was collected to detect and quantify aggrecan levels through Western blotting and determine the relative expression levels of ACAN, IL-1β, IL-6, and TNF-α through qPCR. All affected animals presented chondrodysplasia-like lesions with disorganization of the chondrocyte layers and reduced the amount of an extracellular matrix. No significant difference in aggrecan expression levels in uncleaved samples from the dwarf and control groups (composed of phenotypically normal animals of similar age and breed (P =.7143)) was found using Western blotting. qPCR revealed that ACAN gene expression was higher in the affected animals than in normal animals (P =.0119). No significant difference in cytokine levels was detected between the groups. Mutant aggrecan may interfere with normal cellular function, leading to chondrodysplasia and the observed phenotypic findings.
Keywords: Aggrecan; Chondrodysplasia; Dwarfism; Equine; Real-time polymerase chain reaction; Western blotting